Perancangan Sistem Monitoring dan Kontrol Daya Berbasis Internet of Things - Shodiq, Amir; Baqaruzi, Syamsyarief; Muhtar, Ali (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2021)
Electrical energy is a form of energy that comes from a current source which is usually expressed in Watt hour. The energy used by electrical equipment is the rate at which energy (power) is used for the time the equipment is used. To save the electric power used, consumers must know the electricity consumption every day. To limit usage and estimate electricity usage, therefore consumers must be able to monitor and control the consumption of electric power with a system that is easy and not confusing. One of the current technologies that make monitoring easier is an IoT-based system. PEMoS is a tool designed to monitor and control the consumption of electric power. The device used is equipped with a voltage and current sensor that can read the voltage and current in real time with the NodeMCU communication to send data to the user using the internet network. PEMoS has two parts, namely client and server that communicate wirelessly. The data read by the sensor must first be received by the server before being sent to the cloud server. PEMoS also has an android application which is used to control the client and monitor the electrical power sourced from PLN. After testing the tool, an error value of 1.60% on the voltage sensor reading is obtained, which is still within tolerance limits. For current sensor testing, an error of…. In the communication between the client and the server, there is a delay in sending data for ± 6.